The Relationship between Incoming Patient Conditions with the Death Rate of Covid-19 at Dr. Ramelan Naval Hospital Surabaya - Suhardiningsih, A.V Sri; Rachmawati, Dhian Satya; Setiadi, Setiadi; Budiarti, Enjang Wahyu; Riestiyowati, Maya Ayu (Adpebi International Journal of Multidisciplinary Sciences, 2025)
Covid-19 cases in 2021 continue to increase with a case fatality rate of 7.17% in East Java. Delays in early detection by patients and families, late referrals and stigma related to Covid-19 cases cause patients to come to the hospital with oxygen saturation <80%, so that patients come already in emergency conditions and are at risk of death. Purpose – This study aims to analyze the relationship between the incoming patient conditions with the mortality rate of Covid-19 patients at Dr. Ramelan Naval Hospital Surabaya. Methodology/approach – The research design used cross sectional. The population in this study was 1159 Covid-19 patients who came to the emergency room and who were hospitalized at Dr. Ramelan Naval Hospital Surabaya in May-July 2021. Samples of 174 patients were taken using systematic random sampling techniques. Findings – The results showed that the majority of Covid-19 patients who came for treatment were in moderate symptomatic condition by 67.2%, patients came in critical condition by 29.9% and patients with mild symptomatic condition by 2.9%. The results showed that the death of Covid-19 patients in May-July 2021 was 54 patients (31%).